GASTRONOMIC TOURISM IN ROMANIA - Afrodita BORMA (Annals of the University of Oradea: Economic Science)
Gastronomy, a fundamental component of culture, has become a significant criterion in choosing a tourist destination, playing a crucial role in the development of local economies. By exploring the gastronomy of a region or a country, one can travel through time and space, uncovering the cultural identity of the place. Thus, there is increasing talk of gastronomic destinations that offer tourists dishes with authentic and traditional flavors. Usually, each dish has its own story, describing both the traditional cooking techniques passed down through generations and the use of local ingredients that have defined a community’s cuisine over centuries. These gastronomic experiences are not just about tasting delicious food but also about understanding the history, traditions, and values of a community through its dishes. The connection between tourism and gastronomy is becoming increasingly evident, with tourists eager to taste traditional dishes that provide an authentic perspective on the culture of a tourist destination. Thus, gastronomic tourism involves exploring local cuisine, culinary traditions, markets, and local restaurants to discover and appreciate the diversity and authenticity of the foods and drinks of a region or country. Additionally, culinary tourism may include participating in cooking classes, tastings, culinary festivals, and other gastronomy-related activities, offering travelers the opportunity to gain a deeper understanding of a community’s culture and identity through its food.